'Everywhere I go, you're going with me': Time and space deixis as affective positioning resources in shared moments of digital mourning. (September 2015) - Giaxoglou, Korina
Abstract: This article presents findings from an empirical study of sharing practices on a Facebook memorial site and draws attention to the uses of time and space deixis as affective positioning resources . UsingAndroutsopoulos׳s (2014) framework for the empirical analysis of sharing online, the article examines practices of selecting, styling, and negotiating in significant moments of mourning online, focusing on the entextualizations of a female user shared over the course of a six-month period. The analysis shows how sharers mobilize discursive resources to construct their multifaceted identities as mourners in the local context of the memorial site as well as in the wider situational context of public mourning online. In addition, findings indicate how sharers use time and space deixis to construe spatiotemporal framings and position themselves interactionally and affectively to the dead, the networked mourners, and their digitally entextualized mutable self. It is argued that shifts from static to dynamic construals of time ('tonight' vs. 'everynight') and space ('up there' vs. 'everywhere') are linked to shifts from positions of relative disempowerment to positions of empowerment and agency for the sharer in the context of public mourning. The article offers insights relevant to the study of public mourning in relation to digital performances of self and it contributes to the empirical study of time and space deixis in discourse and participation online.